Emerging Tissue Economies: Personalized Immunotherapies and Therapeutic Value in Cancer. Issue 2 (17th February 2022) - Llewellyn, Henry
ABSTRACT: New personalized immunotherapies hold considerable promise among cancer communities and are touted by many as the future of oncology. Described as a way to enhance the body's "natural defense" against cancer, they are made with antigens taken from patients' own tumor tissue. However, they also set up significant dilemmas for patients who are learning what it is like to participate in an emerging tissue economy and the stakes of exclusion from it. Taking brain tumors as my ethnographic case, I chart the valuations and exchanges that constitute this tissue economy as well as the dilemmas and disparities faced by patients.